ANALYSIS OF THE COMPANY'S POTENTIAL FINANCIAL LOSS IMPACT OF TRADE RECEIVABLES - Dheny Biantara; Iwan Lesmana, S.Kom, MM; Sri Handayani; Bambang Setiono (Universitas Agung Podomoro, 2023)
The problems with receivables faced by the company experienced many obstacles so that inaccurate recording and technology systems that had not been integrated between units became one of the obstacles they faced. This study aims to determine the accounting information system on accounts receivable which is related to its role in the process of sustainable development of a company.The method used in this study is a qualitative - descriptive method. Data collection was carried out by interview, observation and documentation techniques. Data analysis was carried out by means of data reduction, data representation, and drawing conclusions.The results showed that the accounts receivable accounting information system procedures at several companies had different characteristics but remained the same in terms of the problems faced, especially during the past Covid-19 outbreak where many companies, both self-served and government-owned, experienced serious problems in the process of collecting their accounts receivable. .Standard operating procedures for accounts receivable that are clear and separated from existing functions and have a very complete job desk for their parts as well as well-documented records can expedite the process of information on the condition of receivables so that strategic steps can be taken to generate cash inflows for company which will ultimately improve the condition of the company's financial performance to be able to continue to develop sustainably.